2015
DOI: 10.4269/ajtmh.14-0343
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of and Risk Factors for Rhabdomyolysis Among Adult Patients with Dengue Virus Infection

Abstract: Abstract. Among 1,076 dengue patients, 9 patients with rhabdomyolysis and 1,067 patients without rhabdomyolysis (controls) were retrospectively analyzed. Of nine patients with rhabdomyolysis, the most commonly reported symptom other than fever was myalgia; dengue hemorrhagic fever (DHF) was found in seven cases, and acute kidney injury was found in six cases. Furthermore, one (11.1%) patient died. The median duration from hospital admission to rhabdomyolysis diagnosis was 3 days. Patients with rhabdomyolysis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
0
12
0
7
Order By: Relevance
“…To further strengthen the joint reactivity of anti-dsDNA, -nucleosome or -histone antibodies in LN patients, odds ratio (OR) was calculated in different groups of patients within LN or non-LN patients. The OR value greater than one represents a risk factor, whereas less than one a protective factor [ 21 ]. Consistent with our previous results [ 9 ], the group of patients with joint reactivity of the three antibodies (3-pos) not only had the highest number of patients among different LN groups, but also significantly higher than that in non-LN patients, with 41.0% in 921 LN vs 11.2% in 778 non-LN patients, p< 0.001; in addition, 3-pos patients had the highest OR value of 5.529; 95% CI 4.269–7.162, in comparison to other groups with single, double or null reactivity of the three antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…To further strengthen the joint reactivity of anti-dsDNA, -nucleosome or -histone antibodies in LN patients, odds ratio (OR) was calculated in different groups of patients within LN or non-LN patients. The OR value greater than one represents a risk factor, whereas less than one a protective factor [ 21 ]. Consistent with our previous results [ 9 ], the group of patients with joint reactivity of the three antibodies (3-pos) not only had the highest number of patients among different LN groups, but also significantly higher than that in non-LN patients, with 41.0% in 921 LN vs 11.2% in 778 non-LN patients, p< 0.001; in addition, 3-pos patients had the highest OR value of 5.529; 95% CI 4.269–7.162, in comparison to other groups with single, double or null reactivity of the three antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, diabetes with hypertension remained an independent risk factor of severe organ involvement. Hypertension was reported to be a risk factor of rhabdomyolysis28. In addition, diabetes with hyperlipidemia, diabetes with cardiac disorders and cardiac disorders with hyperlipidemia were observed to be independent risk factors of severe organ involvement.…”
Section: Discussionmentioning
confidence: 98%
“…Dengue associated severe organ involvement were cardiovascular18, hepatic141920, renal2122, as well as central nervous systems2324, and to some extent, respiratory252627 and muscular systems2829. Different dengue serotypes may have different severe organ involvements30.…”
mentioning
confidence: 99%
“…Histological analysis revealed circulatory and parenchymal damage, presenting acute tubular necrosis, characterized by desquamation of necrotic cells and loss of the basal membrane mainly in contorted proximal tubules, thrombotic microangiopathy, and glomerulopathy [20,[35][36][37][38]. Studies have reported immune complex-mediated lesion in the glomerulus in patients with DENV infections, and have suggested this as a possible mechanism for urinary abnormalities [39,40]. The histopathological changes observed here exhibited a characteristic lesion of tubular necrosis, seen in cases with co morbidities, such as in diabetes [41].…”
Section: Discussionmentioning
confidence: 99%